Population-level phylogenomic analysis yields insights into species cohesion and population substructure of Lobelia section Lobelia (Campanulaceae) - Grant T. Godden; Andrew A. Crowl; Stephen R. Patten; Princess Abu; Svea Hall; Mark O. Johnston; Douglas W. Schemske; T. Wayne Barger; Miguel A. Pérez-Pérez; Christopher R. Herlihy; Lynda F. Delph; Christopher B. Blackwood; et al. (Molecular Phylogenetics and Evolution, 2025)

Reconciling short- and long-term measurements of coastal cliff erosion rates - Lovleen Acharya-Chowdhury; Mark E. Dickson; Kevin P. Norton; Julie V. Rowland; Brendan Hall; Wayne J. Stephenson (Engineering Geology, 2024)

Assessing daily patterns in stimulant use during the COVID-19 pandemic in Melbourne, Australia using wastewater analysis - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Phong Thai; Chang He; Fahad Ahmed; Qiuda Zheng; Phil M. Choi; Jake W. O’Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

Wastewater-based monitoring of the nitazene analogues: First detection of protonitazene in wastewater - Richard Bade; Dhayaalini Nadarajan; Erin M. Driver; Rolf U. Halden; Cobus Gerber; Alex Krotulski; Wayne Hall; Jochen F. Mueller (Science of The Total Environment, 2024)

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

Assessing the effects of COVID-19 restrictions on alcohol consumption in Melbourne, Australia using high-resolution wastewater sampling - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Michael Livingston; Phong Thai; Chang He; Qiuda Zheng; Nick Crosbie; Jochen Mueller (Science of The Total Environment, 2023)

Prevalence and self-reported reasons of cannabis use for medical purposes in USA and Canada - Janni Leung; Gary Chan; Daniel Stjepanović; Jack Yiu Chak Chung; Wayne Hall; David Hammond (Psychopharmacology, 2022)
Rationale There has been increasing attention on cannabis use for medical purposes, but there is currently a lack of data on its epidemiology. Objectives To examine the epidemiology of self-reported cannabis use for medical purposes by (1) estimating its prevalence, (2) comparing gender and age differences, and (3) investigating what reasons they were used to manage. Methods Participants included 27,169 respondents (aged 16–65) who completed Wave 1 of The International Cannabis Policy Study (ICPS) conducted across Canada and the USA in 2018 via online surveys. Cannabis policy conditions were “US legal–recreational” (legal for both recreational and medical uses), “US legal–medical only”, “US illegal”, and “Canada–medical only”. Results The overall prevalence of self-reported ever cannabis use for medical purposes was 27%, with similar rates by sex and the highest prevalence in young adults. Prevalence was higher in US legal–recreational states (34%) than US illegal states (23%), US legal–medical only states (25%), and Canada (25%). The most common physical health reasons include use to manage pain (53%), sleep (46%), headaches/migraines (35%), appetite (22%), and nausea/vomiting (21%). For mental health reasons, the most common were for anxiety (52%), depression (40%), and PTSD/trauma (17%). There were 11% who reported using cannabis for managing other drug or alcohol use and 4% for psychosis. Conclusions A substantial proportion of the North American population self-reported cannabis use for medical purposes for a variety of medical reasons, including those living in jurisdictions without legal markets. Further research is needed to understand the safety and efficacy of these forms of medical cannabis use.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Contributions of external nutrient loading and internal cycling to cyanobacterial bloom dynamics in Lake Taihu, China: Implications for nutrient management - Hai Xu; Mark J. McCarthy; Hans W. Paerl; Justin D. Brookes; Guangwei Zhu; Nathan S. Hall; Boqiang Qin; Yunlin Zhang; Mengyuan Zhu; Justyna J. Hampel; Silvia E. Newell; Wayne S. Gardner (Limnology and Oceanography, 2021)
Harmful cyanobacterial blooms (CyanoHABs) are linked to increasing anthropogenic nitrogen (N) and phosphorus (P) inputs. However, CyanoHABs in many large lakes continue despite extensive abatement efforts, mostly focused on external P loading. Internal nutrient cycling can modify nutrient availability and limitation; thus, understanding the relative importance of external vs. internal nutrient loading is essential for developing effective mitigation strategies for CyanoHABs. We estimated long‐term nutrient budgets for Lake Taihu, China, from mass balance models using extensive monitoring of input and output nutrient data from 2005 to 2018 to quantify contributions from internal nutrient loading. The nutrient mass balance showed that 9% and 63% of annual external N and P inputs, respectively, were retained in the lake. Denitrification removed 54% of external N loading and can thus help explain rapid decreases in lake N concentrations and summer N limitation. Water column regeneration can help sustain CyanoHABs over the short term and contributed 38–58% of potential demand for summer‐fall, Microcystis ‐dominated blooms. Internal P release contributed 23–90% of CyanoHABs P demand, although Taihu was a net P sink on an annual scale. Our results show that internal nutrient cycling helps sustain CyanoHABs in Taihu, despite reductions in external nutrient inputs. Furthermore, N is leaving the lake faster than P, thereby creating persistent N limitation. Therefore, parallel reductions in external N loading, along with P, will be most effective in reducing CyanoHABs and accelerate the recovery process in this and other large, shallow lakes.

Resolving a paradox—high mercury deposition, but low bioaccumulation in northeastern Puerto Rico - James B. Shanley; Mark Marvin-DiPasquale; Oksana Lane; Wayne Arendt; Steven Hall; William H. McDowell (Ecotoxicology, 2020)

Lower soil carbon stocks in exotic vs. native grasslands are driven by carbonate losses - Brian Wilsey; Xia Xu; H. Wayne Polley; Kirsten Hofmockel; Steven J. Hall (Ecology, 2020)
Global change includes invasion by exotic (nonnative) plant species and altered precipitation patterns, and these factors may affect terrestrial carbon (C) storage. We measured soil C changes in experimental mixtures of all exotic or all native grassland plant species under two levels of summer drought stress (0 and +128 mm). After 8 yr, soils were sampled in 10‐cm increments to 100‐cm depth to determine if soil C differed among treatments in deeper soils. Total soil C (organic + inorganic) content was significantly higher under native than exotic plantings, and differences increased with depth. Surprisingly, differences after 8 yr in C were due to carbonate and not organic C fractions, where carbonate was ~250 g C/m 2 lower to 1‐m soil depth under exotic than native plantings. Our results indicate that soil carbonate is an active pool and can respond to differences in plant species traits over timescales of years. Significant losses of inorganic C might be avoided by conserving native grasslands in subhumid ecosystems.

Effect of Selenium Yeast Supplementation on Naturally Acquired Parasitic Infection in Ewes - Kathryn J. Hooper; Gerd Bobe; William R. Vorachek; Janell K. Bishop-Stewart; Wayne D. Mosher; Gene J. Pirelli; Michael L. Kent; Jean A. Hall (Biological Trace Element Research, 2014)

Effect of Supranutritional Organic Selenium Supplementation on Postpartum Blood Micronutrients, Antioxidants, Metabolites, and Inflammation Biomarkers in Selenium-Replete Dairy Cows - Jean A. Hall; Gerd Bobe; William R. Vorachek; Katherine Kasper; Maret G. Traber; Wayne D. Mosher; Gene J. Pirelli; Mike Gamroth (Biological Trace Element Research, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Effects of Feeding Selenium-Enriched Alfalfa Hay on Immunity and Health of Weaned Beef Calves - Jean A. Hall; Gerd Bobe; William R. Vorachek; Hugejiletu; M. Elena Gorman; Wayne D. Mosher; Gene J. Pirelli (Biological Trace Element Research, 2013)

Selenium Supplementation Alters Gene Expression Profiles Associated with Innate Immunity in Whole-Blood Neutrophils of Sheep - Hugejiletu Hugejiletu; Gerd Bobe; William R. Vorachek; M. Elena Gorman; Wayne D. Mosher; Gene J. Pirelli; Jean A. Hall (Biological Trace Element Research, 2013)

Simian varicella virus open reading frame 63/70 expression is required for efficient virus replication in culture - Elizabeth Brazeau; Mary Wellish; Benedict B. Kaufer; B. Karsten Tischer; Wayne Gray; Fuchun Zhou; Nikolaus Osterrieder; Teri Hanlon; Anjani Golive; Travis Hall; Sreekala Nair; Gregory P. Owens; et al. (Journal of NeuroVirology, 2011)

Establishment of Asian citrus psyllid (Diaphorina citri) primary cultures - Mizuri Marutani-Hert; Wayne B. Hunter; David G. Hall (In Vitro Cellular & Developmental Biology - Animal, 2009)

Professional and personal attitudes of researchers in ageing towards life extension - Mair Underwood; Helen P. Bartlett; Wayne D. Hall (Biogerontology, 2009)

Environmental Factors Contributing to the Development and Demise of a Toxic Dinoflagellate (Karlodinium veneficum) Bloom in a Shallow, Eutrophic, Lagoonal Estuary - Nathan S. Hall; R. Wayne Litaker; Elizabeth Fensin; Jason E. Adolf; Holly A. Bowers; Allen R. Place; Hans W. Paerl (Estuaries and Coasts, 2008)

Using pharmacogenetics and pharmacogenomics in the treatment of psychiatric disorders: some ethical and economic considerations - Katherine I. Morley; Wayne D. Hall (Journal of Molecular Medicine, 2004)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)